2009
DOI: 10.1108/17576380911050043
|View full text |Cite
|
Sign up to set email alerts
|

Banking supervision and nonperforming loans: a cross‐country analysis

Abstract: Purpose -The purpose of this paper is to empirically analyse the cross-countries determinants of nonperforming loans (NPLs), the potential impact of supervisory devices, and institutional environment on credit risk exposure. Design/methodology/approach -The paper employs aggregate banking, financial, economic, and legal environment data for a panel of 59 countries over the period 2002-2006. It develops a comprehensive model to explain differences in the level of NPLs between countries. To assess the role of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
111
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 72 publications
21
111
2
8
Order By: Relevance
“…In a recent study, Mileris (2014) showed that economic deterioration in EU countries with imperfect economic conditions has a negative effect on the debtors' ability to repay their debts. Contrary to the most previous studies, Boudriga et al (2009) using panel data of 59 countries showed that economic conditions seem to have insignificant impact on loan defaults in developed countries. Also, Bucur and Dragomirescu (2014) did not find a significant relationship between credit risk and real GDP growth rate whereas unemployment seems to be positively related to the credit risk in Romanian banking sector over the period 2008-2013. On the other hand, macroeconomic instability would have consequences on the loan quality of banks.…”
Section: Literature Reviewcontrasting
confidence: 45%
“…In a recent study, Mileris (2014) showed that economic deterioration in EU countries with imperfect economic conditions has a negative effect on the debtors' ability to repay their debts. Contrary to the most previous studies, Boudriga et al (2009) using panel data of 59 countries showed that economic conditions seem to have insignificant impact on loan defaults in developed countries. Also, Bucur and Dragomirescu (2014) did not find a significant relationship between credit risk and real GDP growth rate whereas unemployment seems to be positively related to the credit risk in Romanian banking sector over the period 2008-2013. On the other hand, macroeconomic instability would have consequences on the loan quality of banks.…”
Section: Literature Reviewcontrasting
confidence: 45%
“…10 See Bankscope definitions. 11 They used dummy values as proxy of ownership structure. 12 Hu et al [29] found a positive linkage between government-owned banks and NPLs in the Taiwanese banking sector.…”
Section: Macroeconomic Variablesmentioning
confidence: 99%
“…They suggested that high rates of NPLs are generally attributed to high interest rates and the adverse macroeconomic conditions. Moreover, other studies, for example Boudriga et al [10,11]; Berger and Boye [12]; Rinaldi and Sanchis [13]; and Ranjan and Dhal [14] also include macroeconomic determinants as an explanatory variable of NPLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a negative coefficient could signal that banks are not using efficiently their set of diversified derivatives (i.e., futures, options, and swaps) to hedge counterparty credit risks (Jones and Pé rignon, 2013). In that sense, their strategies to transfer such risks to other parties to avoid or reduce the negative impact of such risk and to accept some or all of the consequences of them turns out to be very inefficient (Boudriga et al, 2009;Afriyie and Akotey, 2012). Finally the hypothesis of Chen (2013) also receives statistical support, regarding the negative impact of FLVGR on bank's profitability.…”
Section: Baseline Empirical Analysismentioning
confidence: 99%